Validitas dan Efektivitas Media Karibu Dayak Berbasis Genially pada Materi Klasifikasi Makhluk Hidup SMP - Ru'iyah Ru'iyah; Elsje Theodora Maasawet; Ruqqoyah Nasution; Dora Dayu Rahma Turista; Sri Purwati; Gubtha Mahendra Putra; Marwah Ulwatunnisa (PendIPA Journal of Science Education, 2026)
This study was motivated by students' difficulties in understanding the classification of living things, monotonous science learning, and the limited use of learning media at SMP Negeri 2 Samarinda. The study aimed to determine the validity, practicality, and effectiveness of Genially-based learning media integrated with Dayak Kenyah local wisdom for seventh-grade students. The research employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate). Data were collected through validation sheets, practicality questionnaires, activity observation sheets, and learning outcome tests. The results showed that the learning media achieved a very valid category with an Aiken’s V value of 0.897, a very practical category with an Aiken’s V value of 0.876, and a very feasible category with a percentage of 86.6%. The media was also proven effective, as indicated by an average student activity score of 92%, a paired sample t-test significance value of 0.000, and an N-Gain score of 0.41, which falls into the moderate category. Therefore, the Genially-based learning media integrated with Dayak Kenyah local wisdom is suitable for use in science learning on the topic of the classification of living things.